1998
DOI: 10.1006/viro.1998.9037
|View full text |Cite
|
Sign up to set email alerts
|

Organization of thecis-Acting Element Required for Wheat Dwarf Geminivirus DNA Replication and Visualization of a Rep Protein–DNA Complex

Abstract: Initiation of geminivirus DNA replication depends on the activity of the initiator protein (Rep) upon interaction with DNA sequences present in the intergenic region of the viral DNA. In this study, we have analyzed the DNA sequences present in the large intergenic region (LIR) of wheat dwarf virus (WDV), a subgroup I member of the geminivirus family, which are required for viral DNA replication. We have (i) defined the boundaries of the viral cis-acting DNA replication element, (ii) determined the contributio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

1999
1999
2003
2003

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 51 publications
0
37
0
Order By: Relevance
“…Further deletion analyses have shown that mastreviruses require a large ( 300 bp) cis-acting element for efficient viral DNA replication in cultured cells ( fig. 5; [86]). This element is built up by at least three major components: a central core, 200 bp in size (in WDV between positions − 178/−169 and + 28, taking the A residue at the initiation site as position +1), which is essential for viral DNA replication; the core is flanked by two regions which stimulate replication, the auxiliary regions 5%-aux and 3%-aux, 70 and 25 bp in size, respectively [86].…”
Section: Anatomy Of the ( +)Strand Dna Replication Originmentioning
confidence: 97%
See 2 more Smart Citations
“…Further deletion analyses have shown that mastreviruses require a large ( 300 bp) cis-acting element for efficient viral DNA replication in cultured cells ( fig. 5; [86]). This element is built up by at least three major components: a central core, 200 bp in size (in WDV between positions − 178/−169 and + 28, taking the A residue at the initiation site as position +1), which is essential for viral DNA replication; the core is flanked by two regions which stimulate replication, the auxiliary regions 5%-aux and 3%-aux, 70 and 25 bp in size, respectively [86].…”
Section: Anatomy Of the ( +)Strand Dna Replication Originmentioning
confidence: 97%
“…5; [86]). This element is built up by at least three major components: a central core, 200 bp in size (in WDV between positions − 178/−169 and + 28, taking the A residue at the initiation site as position +1), which is essential for viral DNA replication; the core is flanked by two regions which stimulate replication, the auxiliary regions 5%-aux and 3%-aux, 70 and 25 bp in size, respectively [86]. The 3%-aux region (spanning from + 28 to + 50/+63 in WDV) contains two phased A/T tracts, part of the region conferring a static DNA curvature to the WDV LIR [118].…”
Section: Anatomy Of the ( +)Strand Dna Replication Originmentioning
confidence: 97%
See 1 more Smart Citation
“…However, two members have been described, namely tobacco yellow dwarf virus (Morris et al, 1992) and bean yellow dwarf virus (BeYDV ; , that are adapted to dicotyledonous species. Mutational analysis of open reading frames (ORFs) predicted from the nucleotide sequence, and the identification of a complementary-sense intron has indicated that BeYDV encodes four genes that have functionally conserved homologues in other mastreviruses (Liu et al, a, 1998 Gene expression occurs bidirectionally from the large intergenic region (LIR), which contains cis-acting promoter elements that bind host factors and control virion-sense gene expression (Fenoll et al, 1988(Fenoll et al, , 1990, as well as the origin of virion-sense DNA replication (ori) (Heyraud et al, 1993 ;Heyraud-Nitschke et al, 1995 ;Sanz-Burgos & Gutie! rrez, 1998).…”
Section: Bean Yellow Dwarf Virus (Beydv) and Maize Streak Virus (Msv)mentioning
confidence: 99%
“…It is a single-stranded DNA virus replicating through a rolling circle mechanism in infected monocot plants (Hanley-Bowdoin et al, 2000;Stenger et al, 1991). The essential components of WDV replication are the initiator protein, the (-)strand origin of DNA replication, and the (þ)strand origin of replication (ori) (Sanz-Burgos and Gutierrez, 1998). The Rep protein initiates replication by cutting one strand of the double-stranded viral DNA at the (þ)strand origin of replication, thus generating a free 3 0 -end hydroxyl group that serves as an initiation site for DNA synthesis to be catalyzed by a cellular DNA polymerase and other accessory proteins (Gutierrez, 1999).…”
Section: Introductionmentioning
confidence: 99%